2022
DOI: 10.1016/j.medj.2022.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral metabolite 3′-deoxy-3′,4′-didehydro-cytidine is detectable in serum and identifies acute viral infections including COVID-19

Abstract: Background There is a critical need for rapid viral infection diagnostics to enable prompt case identification in pandemic settings and support targeted antimicrobial prescribing. Methods Using untargeted high-resolution liquid chromatography coupled with mass spectrometry, we compared the admission serum metabolome of emergency department patients with viral infections including COVID-19, bacterial infections, inflammatory conditions, and healthy controls. Sera from an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…Elevated but non-quantitated serum levels of ddhC in COVID-19 patients have been previously reported by Mehta et al (Mehta et al, 2022). Comparable to our results, ddhC showed exceptionally good capacity at distinguishing infected individuals from controls but its relation to disease severity was not so obvious.…”
Section: '4'-didehydro-3'-deoxycytidine (Ddhc)supporting
confidence: 75%
See 1 more Smart Citation
“…Elevated but non-quantitated serum levels of ddhC in COVID-19 patients have been previously reported by Mehta et al (Mehta et al, 2022). Comparable to our results, ddhC showed exceptionally good capacity at distinguishing infected individuals from controls but its relation to disease severity was not so obvious.…”
Section: '4'-didehydro-3'-deoxycytidine (Ddhc)supporting
confidence: 75%
“…Comparable to our results, ddhC showed exceptionally good capacity at distinguishing infected individuals from controls but its relation to disease severity was not so obvious. In the study performed by Mehta et al (Mehta et al, 2022) ddhC was correlated with COVID-19 severity in the discovery cohort but not their validation cohort. In our data we found that the highest levels of ddhC in intermediate COVID-19 severity subgoup.…”
Section: '4'-didehydro-3'-deoxycytidine (Ddhc)mentioning
confidence: 87%
“…Host response to infection can be measured by profiling small molecules (metabolites) and large molecules (proteins). For example, 3′-Deoxy-3′,4′-didehydro-cytidine (ddhC), a human antiviral metabolite, was significantly increased in COVID-19 patients 10 , and Gamma aminobutyric acid (GABA) metabolite was suggested as a potential signaling molecule by activating B cells and plasma cells 11 . We aimed to investigate metabolite and protein profiles to develop a comprehensive snapshot of host response and identify potential molecular biomarkers associated with COVID-19 disease severity.…”
Section: Introductionmentioning
confidence: 99%
“…In the study performed by Mehta et al . (Mehta et al, 2022) ddhC was correlated with COVID-19 severity in the discovery cohort but not their validation cohort. In our data we found that the highest levels of ddhC in intermediate COVID-19 severity subgoup.…”
Section: Discussionmentioning
confidence: 90%